Open Letter to the Pontiff and Vatican Cardinals on Pervasively Corrupt Earth, Planetary, and Astrophysical Science - Herndon, J. Marvin (Advances in Social Sciences Research Journal, 2023)
Five hundred years ago the Roman Catholic Church wrongly opposed science. In my fifty years as a scientist, I have observed the Catholic Church reaching out to science, wholly unaware of widespread corruption and cartel-like behavior under guise of science, which leads, I allege, to the Vatican aiding and abetting activities that are not only anti-Christian, but which pose grave risks to human and environmental health.